The Development of Digital Storytelling Website Based Media for Economic Learning in Senior High School - Lestari, Dini Ayu; Siswandari, Siswandari; Indrawati, Cicilia Dyah Sulistyaningrum (International Journal of Active Learning, 2019)
This study aims to investigate the feasibility of digital storytelling website based media in an effort to improve student economic learning outcomes in Senior High School. The research and development of this web-based digital storytelling media was used the modified Borg & Gall procedure of study. There are three stages of research, namely the introduction, development and hypothesis tested. The target of the research was Senior High School in East Tanjung Jabung, Jambi Province. Data analysis in the development process using descriptive analysis, media feasibility analysis with scale scores and using test analysis of student learning outcomes. the research of the digital storytelling website based media had been developed succesfully to improve the learning outcomes of the 10th Social Sciences Class of Senior High School.